2015
DOI: 10.1007/978-3-662-48350-3_60
|View full text |Cite
|
Sign up to set email alerts
|

Approximation Algorithms for Polynomial-Expansion and Low-Density Graphs

Abstract: We investigate the family of intersection graphs of low density objects in low dimensional Euclidean space. This family is quite general, includes planar graphs, and in particular is a subset of the family of graphs that have polynomial expansion.We present efficient (1 + ε)-approximation algorithms for polynomial expansion graphs, for Independent Set, Set Cover, and Dominating Set problems, among others, and these results seem to be new. Naturally, PTAS's for these problems are known for subclasses of this gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 54 publications
0
23
0
Order By: Relevance
“…Therefore by construction, an r-division of a connected graph G is a collection of connected induced subgraphs of order at most r that cover all edges of G. We will use the terminology from [38]. In particular, the subgraphs in an r-division are termed clusters.…”
Section: Algorithmic Aspects Of R-divisionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore by construction, an r-division of a connected graph G is a collection of connected induced subgraphs of order at most r that cover all edges of G. We will use the terminology from [38]. In particular, the subgraphs in an r-division are termed clusters.…”
Section: Algorithmic Aspects Of R-divisionsmentioning
confidence: 99%
“…It is easy to prove that an r-division can be computed in polynomial time [38]. Next we use the known connections between strongly sublinear separators and polynomial expansion [27] in order to bound the running-time by some truly subquadratic function.…”
Section: Lemma 13 ( [38]mentioning
confidence: 99%
“…More generally, Har-Peled and Quanrud [32] show that local search can be used to obtain PTASs for several problems including independent set, set cover, and dominating set, in graphs with polynomial expansion. These graphs have small separators and therefore r-divisions.…”
Section: R-divisions In Minorsmentioning
confidence: 99%
“…A very different approach is taken by Cabello and Gajser [3] for proper minor-closed classes and more generally by Har-Peled and Quanrud [20] for classes of graphs with polynomial expansion (which by the result of Dvořák and Norin [13] is equivalent to having strongly sublinear separators). They showed that the trivial local search algorithm (performing bounded-size changes on an initial solution as long as it can be improved by such a change) gives polynomial-time approximation schemes for maximum independent and minimum dominating set, as well as many other related problems.…”
Section: Related Resultsmentioning
confidence: 99%